The RPAP3-Cterminal domain identifies R2TP-like quaternary chaperones - Chloé Maurizy (Nature Portfolio, 2018)
R2TP is an HSP90 co-chaperone composed of an RPAP3-PIH1D1 heterodimer, which binds two essential AAA+ ATPases RUVBL1/RUVBL2. Here authors use a structural approach to study RPAP3 and find an RPAP3-like protein (SPAG1) which also forms a co-chaperone complex with PIH1D2 and RUVBL1/2 enriched in testis.